Pengaruh Pemahaman Akuntansi Terhadap Penyusunan Laporan Keuangan UMKM : Studi Pada Kabupaten Kepulauan Aru - Trisna Sary Lewaru; Yustinus Lambyombar; Stivan Harry Uniberua (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This research aims to determine the influence of understanding accounting on the preparation of financial reports for MSMEs in Aru Islands Regency. This type of research is quantitative descriptive which will use primary data obtained from distributing questionnaires to MSMEs in Aru Islands Regency. The number of respondents was 79 MSMEs spread across small islands bordering the Aru Islands Regency. Testing of the hypothesis in this research was carried out using simple linear regression. From the test and analysis results, it is stated that the accounting understanding variable influences the preparation of MSMEs financial reports in the Aru Islands Regency area. Thus, it is important for MSMEs actors to understand accounting in preparing their business financial reports, because if MSMEs actors do not have an understanding of accounting, they will experience difficulties in preparing their business financial reports.